2002
DOI: 10.1530/rep.0.1230837
|View full text |Cite
|
Sign up to set email alerts
|

Influence of uterine bacterial contamination after parturition on ovarian dominant follicle selection and follicle growth and function in cattle

Abstract: First postpartum dominant follicles are preferentially selected in the ovary contralateral to the previously gravid uterine horn. The aim of the present study was to test the hypothesis that uterine bacterial contamination alters the location of ovarian follicle emergence and selection, and inhibits follicle growth and function. Swabs were collected from the uterine body lumen of cattle on days 7, 14, 21 and 28 after parturition. Bacteria were identified by aerobic and anaerobic culture; bacterial growth was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
445
4
17

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 477 publications
(483 citation statements)
references
References 22 publications
17
445
4
17
Order By: Relevance
“…Escherichia coli infect the endometrium within a week of parturition, followed in subsequent weeks by Trueperella pyogenes and a range of anaerobic bacteria that include Fusobacterium, Prevotella and Bacteriodes species (Bonnett et al 1991, Sheldon et al 2002. Although not the focus of the present manuscript, it is important to note that bovine herpesvirus 4 is also tropic for endometrial stromal cells and causes postpartum uterine disease in some animals (Donofrio et al 2007).…”
Section: Microbial Infections Of the Female Reproductive Tractmentioning
confidence: 94%
See 2 more Smart Citations
“…Escherichia coli infect the endometrium within a week of parturition, followed in subsequent weeks by Trueperella pyogenes and a range of anaerobic bacteria that include Fusobacterium, Prevotella and Bacteriodes species (Bonnett et al 1991, Sheldon et al 2002. Although not the focus of the present manuscript, it is important to note that bovine herpesvirus 4 is also tropic for endometrial stromal cells and causes postpartum uterine disease in some animals (Donofrio et al 2007).…”
Section: Microbial Infections Of the Female Reproductive Tractmentioning
confidence: 94%
“…Whilst links between inflammation in the endometrium and infertility are intuitive, it was less obvious whether uterine infections might affect ovarian function. However, in dairy cattle, uterine disease is associated with LPS in follicular fluid, slower growth of dominant follicles, lower peripheral plasma concentrations of oestradiol and increased risks of anoestrus or cystic ovarian disease (Opsomer et al 2000, Sheldon et al 2002. The mechanisms underlying these observations are now emerging.…”
Section: Ovarian Follicle Responses To Bacteria In the Uterusmentioning
confidence: 99%
See 1 more Smart Citation
“…Resumption of cyclicity also occurs during this interval, with the first ovulation occurring around days 40 to 45 postpartum (Cengic et al, 2012). This interval can be affected by nutrition, body condition, parity and can be extended due to uterine disease (Sheldon et al, 2002).…”
Section: Postpartum Uterine Infectionmentioning
confidence: 99%
“…Bacteria can be cultured from samples collected from uterine lumen of dairy cattle in the first 2 weeks after parturition without appearance of any apparent clinical signs (Sheldon et al, 2002). Polat et al, (2009) reported that 10-17% of cows have pathogenic bacteria two weeks post-calving while Sheldon (2007) found that intensively managed dairy cattle often have bacterial uterine contamination rates of 90 to 100% within the first two weeks postpartum.…”
Section: Postpartum Uterine Infectionmentioning
confidence: 99%